The role of farmers’ green values in creation of green innovative intention and green technology adoption behavior: Evidence from farmers grain green production - Gao, Risheng; Zhang, Haitao; Gong, Chunming; Wu, Zhihua (Frontiers in Psychology, 2022)
Grain for Green Project (GGP) is one of China's important ecological restoration projects. The key rationale of this Program is to decrease soil erosion and develop ecological conditions. The agricultural sector is putting efforts to promote green innovation and production among farmers to achieve the targets of ecological restoration projects. However, farmers' green values could play a constructive role in building green innovative intention and green technology adoption behaviors. Based on the unified theory of acceptance and use of technology (UTAUT),the present study investigates the association between farmers’ green values and green technology adoption behavior. For empirical investigation, the current study assumes that farmers’ green values positively correlate with green innovative intention and green technology adoption behavior, respectively. Further, this study proposes that green innovative intention positively impacts green technology adoption behavior. The present study also aims to determine the mediating role of green innovative intention in the relationship between farmer green values and green technology adoption behavior.This study also attempts to check the moderating role of health consciousness in the relationship between farmer green values and green innovative intention and the relationship between farmer green values and green technology adoption behavior, respectively. For empirical analyses, the present study gathered data from 303 farmers in China through a structured questionnaire method using a convenient sampling technique. The present study applied partial least square structural equation modeling for empirically examining hypotheses using Smart PLS software. The findings confirmed that farmers’ green values have a positive association with green innovative intention and green technology adoption behavior, respectively. The results further verified that green innovative intention positively correlates with green technology adoption behavior. The finding also authenticated that green innovative intention positively mediates the relationship between farmers’ green values and green technology adoption behavior. The moderating role of health consciousness in the relationship between farmers’ green values and green innovative intention is also confirmed by the results of this study. However, the findings revealed that health consciousness does not moderate the relationship between farmers’ green values and green technology adoption behavior.